Gazing at the skyline for star scientists. Issue 3 (August 2016) - Sidiropoulos, A.; Gogoglou, A.; Katsaros, D.; Manolopoulos, Y.
Abstract : Highlights: The introduction of the use of skyline operator for scientometric purposes. Establishment of a methodology based on Principal Component Analysis for selecting the dimensions of the skyline operator. Evaluation of the proposed technique for computer scientists. Contrast of the skyline members against those being awarded E.F. Codd award, SIGCOMM Lifetime Achievement award, and Turing award. Abstract: Admittedly, despite the plethora of scientometric indices proposed to rank scientists, none of them can fully capture the performance and impact of a scientist, since each index quantifies only one or a few aspects of his/her multifarious performance. Therefore, the task of scientometric ranking can be seen as a multi-dimensional ranking problem, where the different indices comprise the dimensions. The application of the skyline operator comes then as a natural solution to the problem. In this article we apply the skyline operator to scientist ranking to identify those scientists whose performance cannot be surpassed by others' with respect to all attributes. This technique can be used as a tool for short-listing distinguished researchers in case of award nomination.